Cryptic genetic diversity and associated ecological differences of Anastatus orientalis, an egg parasitoid of the spotted lanternfly - Wu, Yunke; Broadley, Hannah J.; Vieira, Kendra A.; McCormack, John J.; Losch, Corrine A.; Namgung, Hyeban; Kim, Yeongmo; Kim, Hyojoong; McGraw, Alana R.; Palmeri, Marjorie Z.; Lee, Seunghwan; Cao, Liangming; et al. (Frontiers in Insect Science, 2023)
Anastatus orientalis, native to northern China, is an egg parasitoid wasp of the spotted lanternfly (Lycorma delicatula) and is being tested as a potential biological control agent for invasive L. delicatula in the United States. As a component of these evaluations, live A. orientalis collected from Beijing and Yantai in China were reared in containment in the U.S. These specimens showed different responses in diapause behaviors to rearing conditions used previously by other researchers. To understand the primary mechanism potentially driving discrepancies in important life history traits, we used molecular tools to examine the genetic composition of A. orientalis from China and from South Korea, where the parasitoid has been introduced to aid in the population management of invasive L. delicatula. Molecular analysis of mitochondrial DNA recovered six haplotype groups, which exhibit biased frequency of abundance between collection sites. Some haplotypes are widespread, and others only occur in certain locations. No apparent pattern is observed between wasps collected from different years or emergence seasons. Uncorrected genetic distances between haplotype groups range from 0.44% to 1.44% after controlling for within-group variation. Genetic variance of A. orientalis is characterized by high levels of local diversity that contrasts with a lack of a broad-scale population structure. The introduced Korean population exhibits lower genetic diversity compared to native populations. Additionally, we created iso-female lines for major haplotype groups through laboratory rearing. Differences in diapause behavior were correlated with mitochondrial haplotype. Our results indicate that the observed life history traits in A. orientalis have a genetic base.